Cwlwm - Enlli, Ffion (Y Lolfa, 2022)
Living in London, Lydia is struggling through her twenties, regretting drunken nights, reflecting on texts and trying her best nor to be late for work. She has a complicated relationship with Wales. Far from home, she questions her identity and her vision of herself as a Welsh woman in the world. Intro – Pennod 1 – Pennod 2 – Pennod 3 – Pennod 4 – Pennod 5 – Pennod 6 – Pennod 7 – Pennod 8 – Pennod 9 – Pennod 10 – Pennod 11 – Pennod 12 – Pennod 13 – Pennod 14 – Pennod 15 – Pennod 16 – Pennod 17 – Pennod 18 – Pennod 19 – Pennod 20 – Pennod 21 – Pennod 22 – Pennod 23 – Pennod 24 – Pennod 25 – Pennod 26 – Pennod 27 – Pennod 28 – Pennod 29 – Pennod 30.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books